„Chcę serio w świat literacki wyruszyć” — na marginesie listów Michała Borcha do Adama Zawadzkiego - Samborska-Kukuć, Dorota (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2011)
Michael Borch was an author of some important works describing Polish Inflanty (Latgale). In his books, he presented the history and legends of the region, according to the didactic rules required during this period. Borch was a regular correspondent with Zawadzki‘s publishing house. He ordered a lot of historical books from there, on the ground of the topic. This correspondence is a source of knowledge about the problems with particular editions and also Borch‘s personal troubles. Borch was a very important organiser of cultural activities in the area.